Exposure to Nanoplastics Induces an Inflammatory Response in Healthy and Type 2 Diabetic Primary Human Proximal Tubular Epithelial Cells (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.
Keywords: Cardiology; Research